Association of Proteinuria and Incident Atrial Fibrillation in Patients With Intact and Reduced Kidney Function. Issue 7 (6th July 2017) - Molnar, Amber O.; Eddeen, Anan Bader; Ducharme, Robin; Garg, Amit X.; Harel, Ziv; McCallum, Megan K.; Perl, Jeffrey; Wald, Ron; Zimmerman, Deborah; Sood, Manish M.
Abstract : Background: Early evidence suggests proteinuria is independently associated with incident atrial fibrillation (AF). We sought to investigate whether the association of proteinuria with incident AF is altered by kidney function. Methods and Results: Retrospective cohort study using administrative healthcare databases in Ontario, Canada (2002–2015). A total of 736 666 patients aged ≥40 years not receiving dialysis and with no previous history of AF were included. Proteinuria was defined using the urine albumin‐to‐creatinine ratio (ACR) and kidney function by the estimated glomerular filtration rate (eGFR). The primary outcome was time to AF. Cox proportional models were used to determine the hazard ratio for AF censored for death, dialysis, kidney transplant, or end of follow‐up. Fine and Grey models were used to determine the subdistribution hazard ratio for AF, with death as a competing event. Median follow‐up was 6 years and 44 809 patients developed AF. In adjusted models, ACR and eGFR were associated with AF ( P <0.0001). The association of proteinuria with AF differed based on kidney function (ACR × eGFR interaction, P <0.0001). Overt proteinuria (ACR, 120 mg/mmol) was associated with greater AF risk in patients with intact (eGFR, 120) versus reduced (eGFR, 30) kidney function (adjusted hazard ratios, 4.5 [95% CI, 4.0–5.1] and 2.6 [95% CI, 2.4–2.8], respectively; referent ACR 0 and eGFR 120). Results were similar in competing risk analyses. Conclusions: Proteinuria increases the risk of incident AF markedly in patients with intact kidney function compared with those with decreased kidney function. Screening and preventative strategies should consider proteinuria as an independent risk factor for AF.